Types of Indonesian Sentences by Ten Years Old Receptive Child - Yenni Monalisa Gultom; Rahmad . Husein; I Wayan Dirgayasa Tangkas (Universitas Negeri Medan, 2022)
Sentence is very meaningful collection of word, where the sentence can state an idea or idea in full. Sentence is a benchmark for child in their language skills. In writting it can be started with capital letter, and end with a full stop, question mark, or exclamation mark. There are several types of Indonesia sentence that will be disscusss namely declarative sentence, interrogative sentence, imperative sentence, and interjective sentences. A child is said to be receptIve based on several criteria and indicators. This research conducted in a qualitative research, the source of the data from trancribe utterances conversation from daily activity. Technique of the data collection is recoreing, transcribing the sentence, verifying and classifying. This study found that ten years old child were more dominant in interogative that is 26 data (34,6%) sentence and very minimal in declarative sentences that is 9 data (12,1%).